2021
DOI: 10.1002/wmh3.476
|View full text |Cite
|
Sign up to set email alerts
|

How do you solve a problem like Maria? The politics of disaster response in Puerto Rico, Florida and Texas

Abstract: COVID‐19 is not the first, nor the last, public health challenge the US political system has faced. Understanding drivers of governmental responses to public health emergencies is important for policy decision‐making, planning, health and social outcomes, and advocacy. We use federal political disaster‐aid debates to examine political factors related to variations in outcomes for Puerto Rico, Texas, and Florida after the 2017 hurricane season. Despite the comparable need and unprecedented mortality, Puerto Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…This is exemplified by the fact that these restrictions and preconditions were not required of the Government of Texas in the aftermath of Hurricane Harvey. 21 The denial of funds came from more than just the presidency, but also from other agencies of the executive branch. For example, Sommerfeldt (2020) reported that the Department of Housing and Urban Development (HUD) was initially supposed to distribute $9.7 billion in aid to PR in September 2019 to help address the devastation caused by Hurricane María.…”
Section: Us Colonial Anti-corruption Policies After Hurricane Maríamentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by the fact that these restrictions and preconditions were not required of the Government of Texas in the aftermath of Hurricane Harvey. 21 The denial of funds came from more than just the presidency, but also from other agencies of the executive branch. For example, Sommerfeldt (2020) reported that the Department of Housing and Urban Development (HUD) was initially supposed to distribute $9.7 billion in aid to PR in September 2019 to help address the devastation caused by Hurricane María.…”
Section: Us Colonial Anti-corruption Policies After Hurricane Maríamentioning
confidence: 99%
“… 21. For a comparative analysis of the disaster response in PR, Florida, and Texas see, Willison et al (2022). …”
mentioning
confidence: 99%
“…Los modelos sobre cómo los impactos climáticos afectan sistemas complejos y cómo pueden responder las sociedades no suelen tener en cuenta los diversos papeles, identidades y experiencias vividas por las personas, ni las características sociales, políticas y de gobernanza de la toma de decisiones 3,87,88,89,90 . Por ejemplo, la polarización política, además de las desigualdades estructurales, determina cada vez más las respuestas individuales y gubernamentales a los desastres y la planificación a largo plazo 91,92 . Esto puede conducir a un conjunto fragmentario de esfuerzos de mitigación y adaptación en toda una región, lo que puede debilitar el funcionamiento general del sistema 93,94,95 .…”
Section: Mensaje Clave 182 La Complejidad De Los Impactos Y Las Respu...unclassified
“…Twenty US weather and climate disaster events caused 688 fatalities and cost over $1 billion in 2021 (NOAA National Centers for Environmental Information [NCEI], 2022). Willison et al (2021) discuss political determinants of disaster response and disproportionate aid to Puerto Rico and its fragile infrastructure during the 2017 hurricane season. Climate change outcomes, including disasters, migration, and extreme weather, touch the lives of everyone, yet not all are equally prioritized in climate disaster planning and response.…”
Section: Global Health and Climate Justicementioning
confidence: 99%
“…Twenty US weather and climate disaster events caused 688 fatalities and cost over $1 billion in 2021 (NOAA National Centers for Environmental Information [NCEI], 2022). Willison et al (2021) existing and intergenerational inequities (Méndez, 2020). In a recent book review, Daniel-Ulloa (2021, p. 164) remarks on how Michael Méndez's book, Climate Change from the Streets, "builds on the concepts of community-based participatory research and practice to develop equitable policies in climate change legislation, adoption, and implementation.…”
Section: Global Health and Climate Justicementioning
confidence: 99%